2004
DOI: 10.1038/nn1303
|View full text |Cite
|
Sign up to set email alerts
|

Lateral organization of endocytic machinery in dendritic spines

Abstract: Postsynaptic membrane trafficking plays an important role in synaptic plasticity, but the organization of trafficking machinery within dendritic spines is poorly understood. We use immunocytochemical analysis of rat hippocampal neurons to show that proteins mediating endocytosis are systematically arrayed within dendritic spines, tangential to the synapse. Thus, previously unrecognized lateral domains of the spine organize endocytic protein machinery at sites removed from the postsynaptic density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
186
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(200 citation statements)
references
References 15 publications
13
186
1
Order By: Relevance
“…Interestingly, recent studies of mammalian AMPARs indicate that these receptors move laterally and undergo endocytosis in membrane regions that are adjacent to the postsynaptic density (Racz et al, 2004). Thus, one possible explanation for KEL-8 localization adjacent to GLR-1 clusters is that KEL-8 is localized to tangential sites of endocytosis for GLR-1 receptors, similar to what has been observed for mammalian receptors.…”
Section: Kel-8 Is Localized Adjacent To Glr-1mentioning
confidence: 52%
See 2 more Smart Citations
“…Interestingly, recent studies of mammalian AMPARs indicate that these receptors move laterally and undergo endocytosis in membrane regions that are adjacent to the postsynaptic density (Racz et al, 2004). Thus, one possible explanation for KEL-8 localization adjacent to GLR-1 clusters is that KEL-8 is localized to tangential sites of endocytosis for GLR-1 receptors, similar to what has been observed for mammalian receptors.…”
Section: Kel-8 Is Localized Adjacent To Glr-1mentioning
confidence: 52%
“…Although some of the tail sequence signaling elements function to maintain high levels of AMPARs at the synapse, other signaling elements recruit factors that result in the ubiquitination, endocytosis, and proteolysis of AMPARs (Ehlers, 2000;Osten et al, 2000;Burbea et al, 2002;Esteban et al, 2003). AMPARs targeted for destruction are endocytosed in lateral regions adjacent to postsynaptic elements, although the machinery that degrades these membrane-bound proteins is less well understood (Racz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DA receptors, like most GPCRs, internalize via the dynamin-dependent, clathrin-mediated endocytic pathway [43] (Figure 1B). Endocytosis occurs frequently in dendritic shafts, and core endocytic proteins, including adaptor protein 2 (AP-2), clathrin, and dynamin-3, are present in the spine heads [49]. These proteins are systematically arrayed near, but not at, the PSD, to form stable endocytic zones near the PSD in the spine head [30].…”
Section: Local Da Receptor Trafficking In Spinesmentioning
confidence: 99%
“…Furthermore, it has recently been shown that recycling of AMPARs from internal endosomal compartments back to the plasma membrane is important for long-term potentiation (Park et al, 2004). By contrast, endocytosis of AMPARs at sites adjacent to the postsynaptic density is important for long-term depression (Carroll et al, 2001;Racz et al, 2004). Thus, molecular machinery required for endocytosis, as well as intracellular membrane trafficking processes, ultimately regulates the character of signal transmitted at each synapse.…”
Section: Introductionmentioning
confidence: 99%